SMC Scheme for FES Aided Restoration of STS Movement in Paraplegics - Ahmed, Mohammed (International Journal of Integrated Engineering, 2017)
Application of electrical signals for reviving movement functions previously disabled due to diseases or accidents is popularly known as functional electrical stimulation (FES). FES over the years have showed improvement capability in movement restoration, gait rehabilitation and therapy.Â  Annual rise in neurological disorder subjects without same occurring in terms of FES based support devices are worrisome. It could be that more refinement is required to pass clinical stages. Control systems used have been continuously improved in order to meet up with the challenge. The study presents the sliding mode (SM) controller for FES induced sit-to-stand (STS) movement restoration in paraplegics. It can also be applied to other forms of maneuvers and applications. The controller shows robustness in reducing perturbations related and superior tracking ability. Ease of implementation in relation to intelligent methods and presence of mathematical model making advanced analysis easier.Â  The linearized model was used to obtain the PID gains and were utilized for the controller gains using the nonlinear. It was further used as the basis for determining the SM controller parameters. Hence, the sliding mode control (SMC) method have portrayed improved tracking and robustness ability for the FES-aided STS movement revival in paraplegics. The study is novel in the sense such contributions have never been explored for FES induced STS movement restoration application. Therefore, it is expected with further investigations that it might help towards attaining clinical acceptance.